(3GdbhGfjf GdeMceIs - (3CHh GdbGSe Hf eMeO MSjf Gdbej, GdejQRG,J (B1231 (3g` s
(3ChdgG (B:s
(3CeG HYO agPg fHPI ef GdeSGFd GdCUhdjI s
(3BNQgG (B:s
(3hcJH GKHJfGg ai gPg GdUaMGJ ai UMGja GdMSfGJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B183s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B244s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis